LOCAL POWER DYNAMICS: A CASE STUDY OF INTERACTIONS BETWEEN LOCAL GOVERNMENTS AND NON-STATE ACTORS - A Karim, Zamzami; Mandala, Edward (Penerbit Lafadz Jaya, 2024)
This study examines the dynamics of power interactions between local governments and non-state actors in a specific context. The research focuses on the relationships between local governments and non-state actors, such as civil society organizations, private companies, and community groups, to understand how these interactions shape local governance and policy outcomes. The case study is based on empirical research conducted in a selected city, where data was collected through interviews, surveys, and observations. The findings of the study reveal that power dynamics between local governments and non-state actors are complex and multifaceted. Local governments often rely on non-state actors for resources, expertise, and legitimacy, while non-state actors seek to influence policy decisions and access resources. The study highlights the importance of understanding these interactions to better comprehend the dynamics of local governance and policy outcomes. The research contributes to the existing literature on local governance and power dynamics by providing a nuanced understanding of the interactions between local governments and non-state actors. The findings have implications for policy makers, practitioners, and researchers seeking to improve local governance and policy outcomes.